2007
DOI: 10.3201/eid1301.060823
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus gattiiDispersal Mechanisms, British Columbia, Canada

Abstract: C. gattii may be spread through soil disturbances, wind, water, distribution of tree and soil byproducts, and human movement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
107
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 23 publications
5
107
1
Order By: Relevance
“…We have been unable to isolate C. gattii from the environment around his home; therefore, the source of infection remains unclear. C. gattii may have been transiently present in the area at the time of disease acquisition or may be present below the limits of detection, which is consistent with theories of recent dispersal (5,8).…”
supporting
confidence: 73%
“…We have been unable to isolate C. gattii from the environment around his home; therefore, the source of infection remains unclear. C. gattii may have been transiently present in the area at the time of disease acquisition or may be present below the limits of detection, which is consistent with theories of recent dispersal (5,8).…”
supporting
confidence: 73%
“…C. gattii concentrations in air samples obtained during the Vancouver Island outbreak were significantly higher in the warm, dry summer months, although potentially infectious propagules (Ͻ3.3 m in diameter) were present throughout the year (104). Decomposing wood in tree hollows has been identified as an environmental source (22,105).…”
Section: Environmental Studiesmentioning
confidence: 99%
“…Other investigations into the ecological niches of these opportunistic pathogens have revealed a global distribution (Chen et al 2014) often associated with reservoirs such as guano (Nielsen et al 2007), Eucalyptus trees (Ellis and Pfeiffer 1990a), and Cassia trees (Lazera et al 2000; Granados and Castañeda 2005). Furthermore, air sampling in Australia during the flowering season of Eucalyptus camaldulensis contained C. gattii (Ellis and Pfeiffer 1990b) as did air samples collected after tree-cutting activities in Canada (Kidd et al 2007). Finally, Casadevall et al (2003) identified several virulence factors of C. neoformans that are “dual use” with both an environmental survival function and a pathogenetic function: a capsule that provides desiccation resistance as well as production of melanin for UV shielding, heat tolerance, and cold tolerance.…”
Section: Global Aerial Dispersal Of Naganishia Speciesmentioning
confidence: 99%